PENGARUH LAMA PERENDAMAN BENIH KAKAO DALAM AIR KELAPA DAN KOMPOSISI MEDIA TANAM TERHADAP PERKECAMBAHAN DAN PERTUMBUHAN SEMAI BENIH KAKAO (Theobroma cacao,L.) - -, Hyldegardis; Satmalawati, Endah Mulat (Agroprimatech, 2023)
Kakao's seed constitute allergic seed to drying up and will on the downgrade on water and temperature rate that low, upon term harvests or physiological have relative water content tall (rekalsitran). So so long coconut water soaking and media type plants out to regard semai's germination and growth kakao's seed. This research intent to know soaking long time influence kakao's seed in coconut water to kakao's seed germination and media composition plants out to kakao's seed growth, and to get so long soaking and tender plant media composition that nicest for kakao's sprout energy. Was performed at agricultural Faculty garden, Timor's university, with high 400 mdpl, in july August 2022. Utilizing fledged Random Design (RAL) 4x3 is factor, so long soaking (K ) 4 borders without soaking (K 0 ), soaking 6 hours (K 1 ), soaking 12 hours (K 2 ) and soaking 18 hours (K 3 ), both of which is tender plant media composition (M ) 3 borders,   1:1:1 (M1), 1:2:1 (M2) ,2:1:1 (M3), at three times. With conduct combine K0M1, K0M2, K0M3, K1M1, K1M2, K1M3, K2M1, K2M2, K2M3, K3M1, K3M2, K3M3.Longs time observational result soaking coconut water up to 6 hours with tender plant media composition 1:1:1 result best sprout energy. Meanwhile on growth parameter point out soaking long time 18 hours with media composition 2:1:1 high result sprout, total leaf,  fresh weight, maximal dry weight.  Observational result that K2's conduct combine with M1 that, giving more sprout energy maximal.